The Concept of Happiness in the Perspective of QS. Yunus [10]: 62 and Its Correlation with Adolescent Mental Well-being - Agusriana, Sundari; Zulfikar, Eko; Giri Aldi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study delves into the analysis of the concept of happiness as portrayed in the verses of the Quran and its relationship with adolescent mental health. Employing a library research method, relevant literature from Quranic sources and related studies is gathered and analyzed. The primary objective is to identify Quranic verses within Surah Yunus that address the notions of happiness and mental well-being, contextualizing their significance. For this research, a qualitative method was employed utilizing a literature study approach. In this approach, data is gathered from books and journals. Subsequently, the collected data is meticulously analyzed to ensure the precision and accuracy of the research findings. Therefore, this data collection technique is more likely to be literature, literature, namely data collection techniques to review books, notes and various kinds of reports on the problem to be solved. The findings of this investigation reveal that the concept of happiness expounded in QS. Yunus [10]: 62 serves as a guiding principle for adolescents to mitigate mental health issues and alleviate associated symptoms. Consequently, Islamic teachings on self-control exert a profound influence on adolescents, underscoring the importance of acquainting them with the happiness formula elucidated in the Quran to prevent undue distress or excessive worry in the face of adversities. Contribution: This study reveals the role of Surah Yunus verse 62 in shaping adolescent mental resilience based on the concept of happiness in the Quran.